Research on Wireless Internet of Things for Highway Intelligent Transportation System - Henghui Xiao; Jiongcheng Li; Shengpei Ding; Guiyu Li (Dianxin kexue)
For increasing severe traffic conditions, the traditional transportation technology has lost its effectiveness. Intelligent transportation system is a transportation service system based on modern electronic information technology, which is able to use the existing transportation infrastructure effictively, reduce traffic load and environmental pollution, ensure traffic safety and improve transport efficiency. Hence, intelligent transportation system has become a hot spot of research. Based on the technology of LTE and IPv6, application technology of wireless internet of things for highway intelligent transportation system was studied. The detailed framework and implementation plan of highway wireless internet of things were presented, and the corresponding feasibility was demonstrated.